アルミニウム合金抵抗スポット溶接継手の機械的性質に及ぼす異種合金組み合わせの影響 - 樽井, 大志; 松蔭, 武士; 伊與田, 宗慶; 渡部, 良樹 (軽金属溶接, 2025)
In recent years, automobiles have been required to have lighter bodies to reduce CO2 emissions and increase cruising range due to electrification. The application of aluminum alloys which are lighter than steels is expanding. Aluminum alloys can change their material properties with chemical element additives, and different series of aluminum alloys are applied depending on the part or structure of automobiles. In this study, mechanical properties of resistance spot welded joints for dissimilar aluminum alloy were investigated by experiments. We measured joint strengths and hardness distributions of similar A5182 joints, similar A6016 joints and dissimilar A5182 and A6016 joints. These results show that tensile shear strength varies depending on the alloy combination. In addition, the results of different TSS for dissimilar alloy combinations are discussed based on equivalent plastic strain distributions calculated by numerical simulation. In the dissimilar alloy joints, it was confirmed that the equivalent plastic strain was more widely distributed in nugget than in similar alloy joints. It was also found that the contribution of the mechanical properties of each alloy constituting the joint to the wide distribution of that plastic strain was higher than that of the shape of the melted part.